2016
DOI: 10.3803/enm.2016.31.3.469
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Densities Correlated with CXC Chemokine Receptor 4 Expression and Related with Poor Survival in Anaplastic Thyroid Cancer

Abstract: BackgroundTumor associated macrophages (TAMs) and CXC chemokine receptor 4 (CXCR4) have emerged as potential biomarkers in various human cancers. The aims of this study were to investigate the clinical characteristics of anaplastic thyroid cancer (ATC) patients according to the TAM numbers in the tumor tissue, and to evaluate the associations between CXCR4 expressions and macrophage densities in ATC tumor microenvironment.MethodsTotal 14 ATC samples from thyroid tissue microarray were used. Immunohistochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
0
18
0
1
Order By: Relevance
“…In a previous study, the coexistence of lymphocytic thyroiditis was significantly associated with favorable outcomes in papillary thyroid cancer (14). Furthermore, increased TAM infiltration is reportedly associated with poor survival of patients with anaplastic thyroid carcinoma (ATC), the most fatal form of thyroid cancer (15)(16)(17)(18)(19). These studies suggest the important role of the immune system in the progression of thyroid cancer.…”
Section: Introductionmentioning
confidence: 87%
“…In a previous study, the coexistence of lymphocytic thyroiditis was significantly associated with favorable outcomes in papillary thyroid cancer (14). Furthermore, increased TAM infiltration is reportedly associated with poor survival of patients with anaplastic thyroid carcinoma (ATC), the most fatal form of thyroid cancer (15)(16)(17)(18)(19). These studies suggest the important role of the immune system in the progression of thyroid cancer.…”
Section: Introductionmentioning
confidence: 87%
“…CXCL4, CXCL9-10-11 Normal human thyroid cells, human TPC-1 cell line, non-metastatic human PTC (Urra et al 2018) No data available No data available CXCR4 CXCL12 Normal human thyroid cells (González et al 2009), rat RET/PTC thyroid cancer cell line (Castellone et al 2004), human PTC, human ATC, human MTC, human FTC, human ARO cells (He et al 2010, Torregrossa et al 2010, 2012, Shin et al 2013 TAM (Kim et al 2016) Promotion of rat thyroid cancer cell migration (Castellone et al 2004) Promotion of in vitro human anaplastic thyroid cell migration, Association with human metastasis in vivo (Torregrossa et al 2010(Torregrossa et al , 2012) Promotion of EMT (Hwang et al 2003) CXCR7…”
Section: ) Cxcr3mentioning
confidence: 99%
“…It seems worth highlighting that the expression of CXCR4 also influences cell traffic in thyroid cancer microenvironment. Indeed, in anaplastic thyroid cancer (ATC) a significant correlation between CXCR4 expression and numbers of tumorassociated macrophages (TAMs) was reported (Kim et al 2016). CXCL12 induced migration in human thyroid anaplastic carcinoma cell lines (ARO), which was inhibited by an anti-CXCR4 antibody (Hwang et al 2003).…”
Section: Cxcr4mentioning
confidence: 99%
“…It was found that miRNAs (miR-92a, miR-20a, miR-129 and miR-17), CXCR4 and TSP-1 were detectable in EXOs derived from retinoblastoma cells. According to previous studies, miRNAs (miR-92a, miR-20a, miR-129 and miR-17), CXCR4 and TSP-1 are involved in TAM recruitment and proliferation (45)(46)(47)(48)(49)(50)(51). For example, miR-92a stimulates the secretion of the proinflammatory cytokine IL-6 in TAMs, which in turn promotes tumour cell proliferation, invasion and metastasis by interacting with the surrounding microenvironment (46).…”
Section: Discussionmentioning
confidence: 99%
“…However, of note, TSP-1 was detected in EXOs. CXCR4 and TSP-1 are involved in proliferation and TAM recruitment (45)(46)(47)(48)(49)(50)(51). Thus, the contents of EXOs may play a key role in EXO-mediated tumour progression.…”
Section: Constitution Of Exos Derived From Weri-rb1 Cellsmentioning
confidence: 99%